Formation of hollow silica spheres with ordered mesoporous structure by treatment with dimethyl carbonate for selective decomposition of mesoporous silica core - Okamoto, Masaki; Huang, Huimin (Microporous and mesoporous materials, 2012)
[Display omitted] ► Hollow structures were formed by treatment with dimethyl carbonate. ► Radially oriented and ordered mesopores. ► The shell width of the hollow spheres was controllable. ► Phenylanthracene encapsulated in the hollow spheres was slowly released as its vapor. Hollow silica spheres containing ordered mesopores with radial orientation were synthesized from core–shell structured mesoporous silica spheres with pure silica core and propyl group-grafted silica shell. The silica core was selectively impregnated with sodium acetate owing to the hydrophilicity of the core. Sodium acetate acted as a catalyst for silica decomposition with dimethyl carbonate (DMC), and after impregnation, treatment with DMC was performed to remove the core by the reaction of silica with DMC. The obtained hollow spheres contain ordered mesopores with radial orientation and are mono-disperse. The final shell thickness could be controlled by changing the shell thickness of the initial core–shell spheres, as well as by modifying the degree of decomposition of the shell. 9-Phenylanthracene encapsulated in the hollow spheres was gradually released through the mesopores as vapor into an air stream by diffusion limitation.